Tannin-modified magnesium oxychloride cement with high-strength and reinforced water-resistance. (10th November 2022) - Sun, Xinyan; Ye, Qianqian; Zhou, Wenguang; Han, Yufei; Gong, Shanshan; Zhou, Wenrui; Shi, Sheldon Q.; Li, Jianzhang; Fang, Zhen
Abstract: Magnesium oxychloride cement (MOC) has been applied in various fields due to numerous advantages, such as high early strength and low carbon emission. However, the adhibition of MOC has been restricted by the lower waterproofness. Herein in this work, a facile and green approach was come up with to manufacture high-performance magnesium oxychloride cement by the simple organic and inorganic hybrid of tannic acid (TA) and MOC. The fabricated MOC features improved water resistance and compressive strength, surpassing the performances of multiple previous studies, in which only the water resistance was reinforced with the sacrifice of the compressive strength. The excellent performance was ascribed to the chelation between TA and Mg 2+ and the effective filling effect of gel-like phase 5. Such advanced MOC is of great potential in green architecture industry, and this simple and green strategy will give more inspirations for the preparation of high-performance MOC. Graphical abstract: Image 1 Highlights: Magnesium oxychloride cement was modified by the hybrid with tannin. Tannin significantly improved the water resistance and strength. The enhanced mechanism was the chelation of tannin and the filling effect.